Relationship between the users' contact time in educational programs on diabetes mellitus and self-care skills and knowledge - Mariana Almeida Maia; Ilka Afonso Reis; Heloísa de Carvalho Torres (SciELO, 2016)
Abstract OBJECTIVE Check the relationship between the users' contact time in educational programs and self-care and knowledge variables in diabetes mellitus. METHOD A longitudinal study with a quantitative approach with the participation, in the initial phase, of 263 users linked to Basic Health Units in Belo Horizonte, Brazil during the years 2012 and 2013. The data were collected with respect to the total contact time of the users' participation in the educational program as regards knowledge and self-care in acquired diabetes mellitus. The data were analyzed using the Student t-test for comparison of means, considering a 0.05 significance level. RESULTS The final sample included 151 users. The analysis showed that the improvement in self-care scores was statistically higher during an educational intervention of eight hours or more (p-value <0.05). In relation to the scores for knowledge, there was a statistically significant improvement at the end of the educational program. It was not possible to identify a value for the contact time from which there was an increase in mean scores for the ability of knowledge. CONCLUSION To improve the effectiveness of the promotion of skills related to knowledge and self-care in diabetes mellitus, it is necessary to consider the contact time as a relevant factor of the educational program.